Pelatihan Computational Thinking pada Mata Pelajaran bagi Guru Madrasah Pondok Pesantren Selaparang Lombok Berbasis Kurikulum Merdeka - Diah Supatmiwati; Kartarina Kartarina; Ismarmiaty Ismarmiaty; Hilda Hastuti; Wahyu Kamil Syarifaturrahman; Okta Travelian (Jurnal Pengabdian UNDIKMA, 2023)
The aim of this community service is to increase teachers' knowledge and competence related to computational thinking in school subjects and support the program of implementing computational thinking skills for elementary and junior and senior high schools. The method of implementing the service is in the form of a workshop which includes preparation activities, material presentation, and sessions for making CT-based questions. The material is collaborated with existing school subjects such as Mathematics, Language and Social and Physical Science. The target partners of this service are MI and MTs teachers who teach at the Islamic Boarding School of Selaparang Kediri in West Lombok who totaled 31 teachers. In the final session of the activity, an evaluation is carried out using a questionnaire and is analyzed descriptively. The results of this service show that there is an increase in computational thingking knowledge and teachers are able to infuse CT in the subjects they teach.